Efficacy and safety outcomes of long-term anti-thrombotic treatment of chronic coronary artery disease: A systematic review and network meta-analysis - Adawi, Nayrouz; Rotshild, Victoria; Yanko, Stav; Mowaswes, Mohammad; Amir, Offer; Haitner, Gal; Matok, Ilan; Raccah, Bruria Hirsh (Frontiers in Cardiovascular Medicine, 2023)
Background Clopidogrel, prasugrel, ticagrelor, and low-dose rivaroxaban are all optional strategies in conjunction with aspirin for long-term treatment of chronic coronary artery disease. The aim of this research was to assess the efficacy and safety of long-term anti-thrombotic treatment of chronic coronary heart disease. Methods PubMed (MEDLINE), Embase, Clinical Trials Registry ClinicalTrials.gov, and The Cochrane Library were searched through November 2021, to identify randomized controlled trials that compared long term anti-thrombotic therapy for coronary heart disease. Data were extracted to assess eligibility by two independent reviewers. Random-effects meta-analysis was used to pool results. Results Eleven randomized controlled trials were included (88,462 patients). In a network meta-analysis, the rivaroxaban compared to the clopidogrel regimen showed lower relative risks (RRs) for death of any cause (0.71; 95% confidence interval [CI], 0.52–0.96), major adverse cardiac events (MACE) (0.73; 95% CI, 0.57–0.93), and cerebrovascular events (0.48; 95% CI, 0.30–0.78). The RR of cerebrovascular events was also lower for the rivaroxaban compared to the ticagrelor 60 mg regimen (0.72; 95% CI, 0.52–0.99). For the prasugrel regimen, the RRs were lower of myocardial infarction incidence versus all extended strategies: clopidogrel plus aspirin (0.76; 95% CI, 0.58–0.99), rivaroxaban (0.60; 95% CI, 0.38–0.93), ticagrelor 60 mg (0.61; 95% CI, 0.42–0.89), and ticagrelor 90 mg (0.63; 95% CI, 0.41–0.97). None of the dual strategies were associated with differences in major bleeding compared to the prasugrel regimen. Conclusions and relevance The rivaroxaban regimen appeared to be the preferred long-term anti-thrombotic regimen in preventing all-cause mortality. Our available results tend to support the efficacy of extended anti-thrombotic therapy consisting of prasugrel in lowering MI incidence compared to the other strategies, without increased risk of bleeding. However, additional large-scale direct clinical trials are needed to further determine the adequate long-term anti-thrombotic regimens for treating chronic coronary syndrome. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020186583, identifier CRD42020186583.